Tariff Policy for a Monopolist Under Incomplete Information - Thomas J. Prusa; Dobrin Kolev (Rutgers University, Department of Economics, 1998)
We examine the incentives for a government to levy an optimal tariff on a foreign monopolist. With complete information, the home government uses tariffs to extract rents and therefore implements a policy of discriminatory tariffs entailing higher tariffs on more efficient firms. By contrast if the government is incompletely informed about costs, we show that under reasonable conditions the unique self-enforcing outcome involves pooling where firms export the same quantity regardless of efficiency. Due to the distortions created by incomplete information we find that in general, home country welfare is higher under a policy of uniform tariffs than under one of discriminatory tariffs. Our results suggest that trade policies that are motivated by rent extraction are unlikely to be robust to the introduction of incomplete information.
Keywords: 330